Assessment of the impact of CT calibration procedures for proton therapy planning on pediatric treatments. Issue 9 (20th July 2021) - Bär, Esther; Collins‐Fekete, Charles‐Antoine; Rompokos, Vasilis; Zhang, Ying; Gaze, Mark N.; Warry, Alison; Poynter, Andrew; Royle, Gary
Abstract: Purpose: Relative stopping powers (RSPs) for proton therapy are estimated using single‐energy computed tomography (SECT), calibrated with standardized tissues of the adult male. It is assumed that those tissues are representative of tissues of all age and sex. Female, male, and pediatric tissues differ from one another in density and composition. In this study, we use tabulated pediatric tissues and computational phantoms to investigate the impact of this assumption on pediatric proton therapy. The potential of dual‐energy CT (DECT) to improve the accuracy of these calculations is explored. Methods: We study 51 human body tissues, categorized into male/female for the age groups newborn, 1‐, 5‐, 10‐, and 15‐year‐old children, and adult, with given compositions and densities. CT numbers are simulated and RSPs are estimated using SECT and DECT methods. Estimated tissue RSPs from each method are compared to theoretical RSPs. The dose and range errors of each approach are evaluated on three computational phantoms (Ewing's sarcoma, salivary sarcoma, and glioma) derived from pediatric proton therapy patients. Results: With SECT, soft tissues have mean estimation errors and standard deviation up to (1.96 ± 4.18)% observed in newborns, compared to (0.20 ± 1.15)% in adult males. Mean estimation errors for bones are up to (−3.35 ± 4.76)% in pediatrics as opposed to (0.10 ± 0.66)% in adult males. With DECT, mean errors reduce to (0.17 ± 0.13)% and (0.23 ± 0.22)% in newborns (soft tissues/bones). With SECT, dose errors in a Ewing's sarcoma phantom are exceeding 5 Gy (10% of prescribed dose) at the distal end of the treatment field, with volumes of dose errors >5 Gy of V diff > 5 = 4630.7  mm 3 . Similar observations are made in the head and neck phantoms, with overdoses to healthy tissue exceeding 2 Gy (4%). A systematic Bragg peak shift resulting in either over‐ or underdosage of healthy tissues and target volumes depending on the crossed tissues RSP prediction errors is observed. Water equivalent range errors of single beams are between −1.53 and 5.50 mm (min, max) (Ewing's sarcoma phantom), −0.78 and 3.62 mm (salivary sarcoma phantom), and −0.43 and 1.41 mm (glioma phantom). DECT can reduce dose errors to <1 Gy and range errors to <1 mm. Conclusion: Single‐energy computed tomography estimates RSPs for pediatric tissues with systematic shifts. DECT improves the accuracy of RSPs and dose distributions in pediatric tissues compared to the SECT calibration curve based on adult male tissues.